Eduard C. Lindeman analyzes the farmer's cooperative marketing movement in 1923. Issue 3 (3rd July 2021) - Stuart, Paul H.; Rodriguez, Maria Y.
ABSTRACT: This "From the Archives" article provides the text of Eduard C. Lindeman's 1923 article on the farmer's cooperative marketing movement. The article was published in the May, 1923, issue of the Journal of Social Forces, vol. 1, no. 4, pp. 447–450.